Clinical study of myoclonic epileptic syndromes - Goli, Nikhil; Koguru, Srikanth; Wadia, Rustom S.; Agarwal, Sanjay; Patel, Pradeep; Reddy, Pradeep; Nallam, Karthik; Kharwade, Datta (International Journal of Advances in Medicine, 2016)
Background: Incidence of different myoclonic epileptic syndromes is variable in different regions. Here in as there is very few literature available internationally being inclusive of all myoclonic epilepsies together. Very few studies are available which describe all characteristics in a given study population. The aim of the study was to find incidence of different types of myoclonic epilepsies among patients presenting with myoclonic seizures their characteristics and to study all myoclonic epilepsies and juvenile myoclonic epilepsy in the study population. Methods: In this study conducted in neurological unit at Ruby hall clinic, a total of 188 case of epileptic disorder were enrolled irrespective of age and sex, among 136 were new case of epileptic disorder were classified based on seizure pattern, 23 were new cases of myoclonic epilepsy, these 23 new case of myoclonic epilepsy along with 52 old cases of myoclonic epilepsy attending to neurological unit were clubbed, a total of 75 cases myoclonic epilepsy were studied. All cases of myoclonic epilepsy and juvenile myoclonic epilepsy were studied with respect to age of onset different seizures, relation with family history, response to treatment, EEG findings. Results: Out of 136 cases 23 were new cases of myoclonic epilepsy, these 23 newly diagnosed cases of myoclonic epilepsies along with 52 already diagnosed myoclonic epilepsy are clubbed together, total of 75 cases were further studied. Incidence of myoclonic epilepsy among epileptic patients found to be 16.9%. Incidence of JME among myoclonic epilepsies is 75-80%, in all myoclonic epilepsies and JME association with GTCS, family history, EEG abnormalities were common finding, valproate and leviteracetam are good therapeutic options, carbamazepine aggravated myoclonus. Conclusions: For diagnosis of myoclonic epilepsy proper clinical history stress laid to ask history of myoclonic jerk in case of all seizure disorder, diagnosis basically depends on proper knowledge of myoclonic epileptic syndrome, eliciting history, EEG as an ancillary testing when in doubt always expert opinion is required as misdiagnosis of the myoclonus as partial seizure leads to wrong prescription of carbamazepine which exacerbates the myoclonus.